Verification of electronic device technology for measurement and evaluation of thermal exposure of fire fighters and members of rescue teams - Šárka Bernatíková; Hana Tomášková; Marek Bužga; Zdeněk Jirák; Petr Novák; Ján Babjak; Tomáš Kot; Václav Krys; Ladislav Jánošík (Nofer Institute of Occupational Medicine, 2018)
Background The work of members of rescue teams could be associated with very high physical and thermal loads. If not timely interrupted, any extreme labour-thermal load may lead to a failure of the body and fatal collapse. This risk may be significantly reduced by devices that monitor the response of the body during the intervention and inform rescuers about the need to interrupt the exposure when the critical value of the reference indicator is achieved. The aim of the study was to test the correlation between the data of the newly developed device for signaling the strain of rescuers and the indicators of physiological response of the body. Material and Methods The tests were performed on 2 physically fit fire fighters dressed in a protective rescue suit and using insulating breathing apparatus, over a wide range of heat load under a model load on a bicycle ergometer in a climatic chamber. Results The study provided a significant correlation between the body temperature measured in the ear canal and the temperature under the suit sensed by the tested device - the Safety Ambient Monitor (SAM) (R = 0.9007). The temperature under the suit also correlated with the temperature of the chest skin (R = 0.8928) and heart rate (R = 0.8613). Conclusions A statistically significant correlation was proven between the temperature sensed by the SAM and the body temperature. The technical solution of sensing the temperature under the suit using the verified SAM technology does not affect or limit fire fighters in their work and minimizes the possibility of damage to the sensor and signaling failures. Med Pr 2018;69(1):1-11